Reform of Life Imprisonment in Lithuania - Namavičius, Justas (Teisė, 2023)
This article discusses the 2019 reform of criminal laws, providing for the possibility of releasing persons sentenced to life imprisonment. The legislator, establishing the model of punishment substitution instead of parole, chose a sufficiently strict regulation, and although he declared otherwise, he did not really dare to go beyond punishment as a retribution for extremely serious crimes. In addition to the historical development of life imprisonment and aspects of the theory of punishment, the work also focuses on individual release criteria; at the end, possible directions of reform are briefly defined.